LncRNA-mediated cartilage homeostasis in osteoarthritis: a narrative review - Zhang, Li; Zhang, Hejin; Xie, Qian; Feng, Haiqi; Li, Haoying; Li, Zelin; Yang, Kangping; Ding, Jiatong; Gao, Guicheng (Frontiers in Medicine, 2024)
Osteoarthritis (OA) is a degenerative disease of cartilage that affects the quality of survivallife and has increased in morbidity and mortality in recent years. Cartilage homeostasis and dysregulation are thought to be important mechanisms involved in the development of OA. Many studies suggest that LncRNAslncRNAs are involved in cartilage homeostasis in OA and that LncRNAslncRNAs can be used to diagnose or treat OA. Among the existing therapeutic regimens, LncRNAslncRNAs are involved in drug-and nondrug-mediated therapeutic mechanisms, which and are expected to improve the mechanism of adverse effects or drug resistance. Moreover, targeting LncRNAtargeted lncRNA therapy may also prevent or treat OA. The purpose of this review is to summarize the linklinks between LncRNAslncRNAs and cartilage homeostasis in OA. In addition, we review the potential applications of LncRNAslncRNAs at multiple levels of adjuvant and targeted therapies. This review highlights that targeting LncRNAslncRNAs may be a novel therapeutic strategy to improve and modulatefor improving and modulating cartilage homeostasis in OA patients.